2022
DOI: 10.1186/s12974-022-02496-w
|View full text |Cite
|
Sign up to set email alerts
|

The role of Toll-like receptors and neuroinflammation in Parkinson’s disease

Abstract: Background Parkinson’s disease (PD) is the second most prevalent neurodegenerative disorder, characterized by motor and non-motor symptoms, significantly affecting patients’ life. Pathologically, PD is associated with the extensive degeneration of dopaminergic neurons in various regions of the central nervous system (CNS), specifically the substantia nigra. This neuronal loss is accompanied by the aggregation of misfolded protein, named α-synuclein. Main text … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(78 citation statements)
references
References 155 publications
3
75
0
Order By: Relevance
“…There is a growing body of evidence supporting a role for TLR4 in Parkinson's disease [55]. TLR4 expression is high in the substantia nigra in association with Parkinson's disease, along with upregulation of the inflammatory cytokine IL-1β [56].…”
Section: Cd16+ Monocytes and Toll Like Receptormentioning
confidence: 99%
“…There is a growing body of evidence supporting a role for TLR4 in Parkinson's disease [55]. TLR4 expression is high in the substantia nigra in association with Parkinson's disease, along with upregulation of the inflammatory cytokine IL-1β [56].…”
Section: Cd16+ Monocytes and Toll Like Receptormentioning
confidence: 99%
“…Its activation triggers the host in ammatory response and the proin ammatory factors, including TNF-α, IL-1β, and IL-6 [47,48,49]. These ndings revealed that gut microbiota might drive the colonic mucosa immunological activation via the TLR4 signaling pathway, resulting in neuroin ammation and further neurodegeneration in PD [50]. To further explore the mechanism by which CDG exerts neural protection by replenishing the intestinal microbiota of PD mice, we highlighted the relationship of in ammation between the gut and the brain.…”
Section: Discussionmentioning
confidence: 94%
“…There is a growing body of evidence supporting the role of TLR4 in PD [ 85 ]. TLR4 expression is high in the substantia nigra in association with PD, along with upregulation of the inflammatory cytokine IL-1β [ 86 ].…”
Section: Reviewmentioning
confidence: 99%